Assessing Electronic Service Delivery in Municipalities - Tjerk Budding; Bram Faber; Raymond Gradus (Tinbergen Institute, 2017)
In the Netherlands, electronic service delivery has become an important issue in many municipalities. Using the Internet for service delivery is seen as an important element of e-government. Based on 2014-2016 panel-data of ICT service delivery for all Dutch municipalities, we show that there is a large variety among the municipalities in the extent to which they offer their service delivery digitally. We explore the factors that may explain the differences among the municipalities. Some trends can be discerned, most notably the strong relationship of e-government adoption with demographic characteristics, such as population, population density and both older age and younger age groups. Remarkably, we did not find an influence of educa-tion and income. Finally, we did not observe a relation between municipal allocated costs and level of e-maturity, hereby leaving the question open if and how e-government can lead to cost reductions.
Keywords: M15; H76; H79; 330; e-government; municipalities; service delivery; local government; cost of services; empirical study